Efektivitas Implementasi E-SAKIP Dalam Meningkatkan Kinerja Rumah Sakit Publik: Studi Kasus RSUD Kelas A di Indonesia - Rinadini Hendrasworo (Policy and Maritime Review, 2025)
The implementation of E-SAKIP in public hospitals faces significant challenges due to service complexity, limited resources, and high service quality demands. Public hospitals are expected not only to provide optimal healthcare services but also to be accountable for the use of public resources. Despite the high urgency of implementing E-SAKIP, its implementation is still hindered by issues such as limited human resource capacity, complex reporting procedures, resistance to change, and the suboptimal integration of digital systems with organizational work practices. This study aims to analyze the effectiveness of E-SAKIP implementation in improving the performance of public hospitals, focusing on a case study of a Class A Regional General Hospital (RSUD) in Indonesia. A descriptive qualitative approach is used, with data collection techniques including document study, observation, and literature review. The findings indicate that although E-SAKIP implementation has had a positive impact on performance improvement and internal coordination, there are still significant challenges related to human resources and reporting complexity.